Open Data Parliament: Implementation And Challenges In Indonesia - Prihandini, Natasya Arnanda; Muslim, Muh Azis (Journal Research of Social Science, Economics, and Management, 2023)
Open Parliament is a movement that encourages transparency, participation, and accountability in the legislative process in parliament. One form is data openness, which is a tool for the public to understand the programs and performance of the legislature. Data disclosure in parliament is also carried out to answer public unrest over parliament's attitude which is considered closed in discussing legislation products. The research will reveal how parliamentary data disclosure has been running in Indonesia and other countries, namely Norway, Sweden, and Denmark. The research paradigm is carried out qualitatively and to answer research questions, data collection methods use interviews and literature studies. The results of the study revealed that data openness in Indonesia currently does not fully meet the principles of government data openness, namely primary, timely, license-free, non-discriminatory, and supports the data processing process using machines. Therefore, the Indonesian Parliament needs to make efforts to improve data disclosure services based on the above principles, with the aim of providing easy access to data and meeting people's data needs.